In the Footsteps of Dante. Comments on I. Brodsky’s Poem "December in Florence" - TATEVOSYAN, ANAIT (Bulletin of Yerevan University H: Russian Philology, 2021)
I.Brodsky’s poem "December in Florence" reproduces not only the content but also the structure of Dante’s Hell, its nine stanzas correspond to the nine circles of hell, Florence includes all nine circles, but the title of the poem underlines its correspondence to the icy ninth circle, where traitors are punished. Throughout the poem Dante’s and Brodsky’s biographies intersect, Florence coincides with St. Petersburg, but the last stanza describes the personal hell of Brodsky – his own city.